Are early proteomic and metabolic changes induced by long-term sugar-sweetened beverage consumption the key to unlocking the cardio-metabolic pandemic? - Benade, Janina (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.